Comparative genomic hybridisation using a proximal 17p BAC/PAC array detects rearrangements responsible for four genomic disorders. Issue 2 (2nd February 2004) - Shaw, C J; Shaw, C A; Yu, W; Stankiewicz, P; White, L D; Beaudet, A L; Lupski, J R
Abstract : Background: Proximal chromosome 17p is a region rich in low copy repeats (LCRs) and prone to chromosomal rearrangements. Four genomic disorders map within the interval 17p11–p12: Charcot–Marie–Tooth disease type 1A, hereditary neuropathy with liability to pressure palsies, Smith–Magenis syndrome, and dup(17)(p11.2p11.2) syndrome. While 80–90% or more of the rearrangements resulting in each disorder are recurrent, several non-recurrent deletions or duplications of varying sizes within proximal 17p also have been characterised using fluorescence in situ hybridisation (FISH). Methods: A BAC/PAC array based comparative genomic hybridisation (array-CGH) method was tested for its ability to detect these genomic dosage differences and map breakpoints in 25 patients with recurrent and non-recurrent rearrangements. Results: Array-CGH detected the dosage imbalances resulting from either deletion or duplication in all the samples examined. The array-CGH approach, in combination with a dependent statistical inference method, mapped 45/46 (97.8%) of the analysed breakpoints to within one overlapping BAC/PAC clone, compared with determinations done independently by FISH. Several clones within the array that contained large LCRs did not have an adverse effect on the interpretation of the array-CGH data. Conclusions: Array-CGH is an accurate and sensitive method for detecting genomic dosage differences and identifying rearrangement breakpoints, even in LCR-rich regions of the genome.